PENGARUH PENGELUARAN PEMERINTAH DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DAN KESENJANGAN PENDAPATAN KABUPATEN/KOTA DI PROVINSI BALI - Wahyuni, I Gusti Ayu Putri; Sukarsa, Made; Yuliarmi, Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
ABSTRACT Economic growth requires a strong commitment from the government and private parties. The realization of the role of government and the private sector is done through government spending and investment. The role of government in economic growth is in the provision of public goods. While the investment required to drive human resource factors, process natural resources and technological innovation updates. Those, economic growth can improve the welfare of society that will impact the income gap. This study aimed to analyze the effect of government spending and investment on economic growth and income inequality district / city of Bali Province in 2000-2012. The data used are secondary data obtained from the Central Statistics Agency ( CSA ) of Bali and other related agencies. The analysis technique used is the analysis of the path or path analysis. This study concludes that government spending and investment from the year 2000-2012 and a significant positive effect on economic growth in the district / town in the province of Bali. Government spending, investment and economic growth is also positive and significant effect on income inequality districts/ cities in the Province of Bali. Besides spending a significant effect on economic growth in the income gap through district/ city in the province of Bali. Investment income gap significantly influence economic growth through the district/ city in the province of Bali. The existence of a significant effect of government spending, investment and economic growth on income inequality directly or indirectly, indicate that the determination necessary to study the distribution and allocation of investment expenditures are evenly so as to promote economic growth and can reduce the income gap. Keywords: Expenditures, Investment, Economic Growth and Income Inequality. Normal 0 false false false EN-US X-NONE X-NONE
Keywords: Expenditures, Investment, Economic Growth and Income Inequality